Novel behavioral tasks for the measurement of social motivation in mice: a comparison across strains - Wells, Caitlyn; Huddleston, Kendall P.; Brown, Steven; Razzaq, Fatima; Chick, Donald; Rogers, Tiffany D. (Frontiers in Behavioral Neuroscience, 2026)
IntroductionSocial isolation, reduced social interaction, and social anhedonia are associated with a range of neuropsychiatric conditions. While the search for novel pharmacological agents to treat social symptoms persists, more precise social behavior measures in pre-clinical animal models are needed to make the most accurate predictions of therapeutic outcomes.MethodsIn the current study, we propose two novel behavioral tasks to measure social motivation in mouse models. We define social motivation as the willingness to exert effort to access a social partner. The first social motivation test, the weighted door task, requires a mouse to push open a one-way, weighted door that increases in weight across successive trials to access a social partner behind the door. The second social motivation test, the ladder task, requires a mouse to climb a ladder that increases in steepness across trials to access a social partner on a platform at the top of the ladder. To validate these tasks, we compared behavioral outcomes across three common inbred strains, C57BL/6J, DBA/2J, and BTBR T + Itpr3 tf /J. Social motivation outcomes were then compared to outcomes in two standard social behavior tests: the three-chamber task and the free dyadic social interaction task.ResultsFollowing behavioral testing, we found that each strain displayed distinct behavioral responses in social motivation tasks with BTBR mice demonstrating low social motivation, DBA mice demonstrating high social motivation, and C57 mice demonstrating conditionally high social motivation during low effort trials.DiscussionWhen combined with standard social behavior testing, our measures provide more detailed social behavior phenotypes unique to each strain. In addition to allowing the creation of more complete social behavior ethograms, these tasks offer advantages as compared to existing conditioning-based behavior tasks measuring social motivation and reward such as the social conditioned place preference task and operant conditioning for social reward. The weighted door and ladder tasks leverage innate exploration behaviors that do not require prior learning which allows for more models, including those with memory, attention, and learning deficits, to be used. These pre-clinical measures of social motivation may prove useful in improving predictions of social behavior outcomes of proposed pharmacological interventions for clinical populations.